A case of pyometra with a colouterine fistula due to rectal cancer presenting as acute abdomen. Issue 8 (26th August 2020) - Kanemura, Masanori; Yoshida, Atsushi; Toji, Akihiko; Hashida, Sousuke; Murayama, Yumi; Iwai, Emi
Abstract: Pyometra usually develops in elderly women, and it can be caused by various etiologies. We describe a rare case of pyometra with a colouterine fistula due to rectal cancer presenting as acute abdomen. A 67-year-old woman with purulent vaginal discharge and abdominal distension was referred to our hospital for suspected pyometra. Because the vaginal echogram showed pyometra at her initial medical examination, drainage was performed. Her symptoms subsequently disappeared temporarily, but 4 months later, she developed acute abdomen. The computed tomography scan showed a pelvic mass with expansion of the intestine. The patient underwent en bloc resection of the mass. Histopathologic analysis of the tumor showed rectal cancer with invasion of the uterus and ileum, and a colouterine fistula. Although pyometra due to a colouterine fistula is a very rare condition, the incidence of associated malignancy is considerable. Physicians should be aware of this potential presentation of colorectal cancer.